Young People on Social Media: The Implications of Child Influencers in Vietnam - Nguyen Do Doan Hanh (Social Media + Society)
This article examines the implications of Vietnamese child influencers, focusing on how they embody and perform local cultural norms to build and sustain their personas on social media platforms. Vietnamese childhood is shaped by traditional values that embrace academic diligence. Drawing on digital ethnographic methods, I examine two case studies: one of a female child YouTuber, and another of an adult livestreamer who is widely misperceived as a 10-year-old boy. The article suggests that cultural ideals related to filial piety of academic diligence, and enactments of cuteness inform audience expectations of Vietnamese child influencers. Thus, they are expected to be studious or produce content related to study, and to be cute. The article further concluded that, with the monetization opportunities offered by platforms, child influencers may take responsibility to be financial supporters, a duty that only adults are expected to do. In doing so, they extend the practice of filial piety beyond being studious.